Evolution of the viscoelastic properties of SnO2 colloidal suspensions during the sol-gel transition - Tokumoto, Miriam S. [UNESP]; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Elsevier, 2000)
This paper describes the effect of the concentration of electrolyte and pH on the kinetics of aggregation and gelation processes of SnO2 colloidal suspensions. Creep, creep-recovery, and oscillatory rheological experiments have been done in situ during aggregation and gelation. A phenomenological description of the structure of the colloidal system is given from the time evolution of rheological parameters. The dependence of the equilibrium steady-state shear compliance on the terminal region of clusters or aggregates seems to be a way to determine the beginning of interconnection of aggregates and the gel point. We propose that at this point the equilibrium steady-state compliance is a minimum. The steady-state viscosity determined from creep experiment can be fit with a power law with the extent of the transformation, giving critical exponent s = 0.7 ± 0.1. The value of the critical exponent Δ = 0.78 ± 0.05 was determined from oscillatory experiment. These results indicate that gelation of SnO2 colloidal suspension exhibits the typical scale expected from the scalar percolation theory. © 2000 Elsevier Science B.V. All rights reserved.